1988
DOI: 10.1021/bi00417a058
|View full text |Cite
|
Sign up to set email alerts
|

Structural comparison of two serine proteinase-protein inhibitor complexes: Eglin-C-subtilisin Carlsberg and CI-2-subtilisin Novo

Abstract: The crystal structures of the molecular complexes between two serine proteinases and two of their protein inhibitors have been determined: subtilisin Carlsberg with the recombinant form of eglin-c from the leech Hirudo medicinalis and subtilisin Novo with chymotrypsin inhibitor 2 from barley seeds. The structures have been fully refined by restrained-parameter least-squares methods to crystallographic R factors (sigma[[Fo[ - [Fc[[/sigma[Fo[) of 0.136 at 1.8-A resolution and 0.154 at 2.1-A resolution, respectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
237
1

Year Published

1990
1990
1999
1999

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(247 citation statements)
references
References 61 publications
9
237
1
Order By: Relevance
“…The structure consists of a well defined rigid core, with an cl-helix on one side, a four stranded B-sheet and a binding loop with high mobility. Eglin c is a member of the potato inhibitor family [25] where the homologous structure of the proteinase inhibitor CI-2 from barley seeds has been determined in complex with proteinases by X-ray crystallography [26]. The structure of eglin in the crystal is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The structure consists of a well defined rigid core, with an cl-helix on one side, a four stranded B-sheet and a binding loop with high mobility. Eglin c is a member of the potato inhibitor family [25] where the homologous structure of the proteinase inhibitor CI-2 from barley seeds has been determined in complex with proteinases by X-ray crystallography [26]. The structure of eglin in the crystal is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…CPhilipp and Bender (1983);Carter et al (1989). dInferred from inspection of X-ray structures (Robertus et al, 1972;McPhalen & James, 1988) and from Morihara et al (1970). CCarter and Wells (1987).…”
Section: N F I B Itormentioning
confidence: 99%
“…subtilisin BPN' (Hirono et al, 1984;McPhalen et al, 1985;McPhalen and James, 1988;Heinz et al, 1991;Takeuchi et al, 1991a,b), subtilisin Carlsberg (Bode et al, 1986;McPhalen and James, 1988), subtilisin BL (Godette et al, 1992), high-alkaline protease (Betzel et al, 1992;Sobek et al, 1992; Van der Laan et al, 1992;Lange et al, 1994), mesentericopeptidase (Dauter The pro-nisin part is fully modified, as indicated by the modified residues. Dha, dehydroalanine; Dhb, dehydrobutyrine; Ala-S-Ala, lanthionine; Abu-S-Ala, β-methyllanthionine.…”
Section: Introductionmentioning
confidence: 99%
“…Residues in subtilases that are in contact with substrate or inhibitor have been identified from crystal structures and modelling of enzyme-inhibitor complexes (Hirono et al, 1984;McPhalen et al, 1985;Bode et al, 1987;Betzel et al, 1988bBetzel et al, , 1993McPhalen and James, 1988;Gros et al, 1989;Dauter et al, 1991;Heinz et al, 1991;Takeuchi et al, 1991a,b) and enzyme-substrate complexes (Wells et al, 1987a), and from protein engineering studies of subtilisin BPN' (Estell et al, 1986;Wells et al, 1987a,b). In each case the mode of substrate-inhibitor binding appears to be essentially the same, and this provides a sound basis for predicting enzyme-substrate interactions in other members of this family.…”
Section: Introductionmentioning
confidence: 99%